Buddhism, reincarnation, and Dalai Lamas of Tibet / (Acc. 4062) - Chitkara, M. G., 1932- (New Delhi : A.P.H. Pub. Corp., 1998)
Tibetan Buddhist theory of reincarnation based on the system of recognizing the Dalai Lamas.
Keywords: Reincarnation; Dalai Lamas